If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (-1) = 7 4x + -1 = 7 Reorder the terms: -1 + 4x = 7 Solving -1 + 4x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4x = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 4x = 7 + 1 4x = 7 + 1 Combine like terms: 7 + 1 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| x^2+4+15=-8x+4 | | 4a-6=7a-9 | | 8(x-2)-9=6x+7 | | 6(2x-7)=3(5x+6) | | 5/9x(77-32) | | 1.1+lnx^2=6 | | 4x^2+8x-44=16 | | -4.76-4.8t=9.7(t+2.2) | | 3=y/4-10 | | 3/2-5/6-2/9 | | y/3-11=7 | | 56=4u+8 | | a/a-3=4/3 | | a-9=4a+3 | | 2.9(x+8.7)=7.6x-0.15 | | 2cos^2x+4cosx+3=0 | | .5x=4.6 | | 1.5(y-4)=1.9-y | | -(6x-9)=9 | | f(-5)=3.5x-6 | | 7x-8=7-31 | | f(-5)=3.5-6 | | 8=21p/100 | | 12y+13-3y-7= | | f(x)=3.5x-6 | | 4/q=5 | | X=6.2(180-x) | | 7(-6+-5)=(7*g)+(7*-5) | | 16x+3x+2x+x= | | 4a+8=2a-6 | | (2/7n-3m)^2 | | y=log(13-x) |